2022
DOI: 10.1007/s11707-022-0969-2
|View full text |Cite
|
Sign up to set email alerts
|

Fractal characterization of pore structure and its influence on CH4 adsorption and seepage capacity of low-rank coals

Abstract: The pore structures of coal can directly affect the adsorption and seepage capacity of coalbed methane (CBM), which therefore is an important influence on CBM exploration and development. In this study, the pore structures of low-rank coals from the Middle Jurassic Xishanyao Formation in the southern Junggar Basin were analyzed, and the fractal dimensions (D1, D2, D3 and D4 corresponding to pore sizes of 0−5 nm, 5−100 nm, 100−1000 nm and 1000−20,000 nm, respectively) were calculated to quantitatively describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Both coal seams belong to medium-rank coal. Previous studies have shown that the gas content increases with the coal rank, , which can be attributed to the increase of micropore and pore specific surface area . The No.…”
Section: Coal-bearing Strata and Coal Seam Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…Both coal seams belong to medium-rank coal. Previous studies have shown that the gas content increases with the coal rank, , which can be attributed to the increase of micropore and pore specific surface area . The No.…”
Section: Coal-bearing Strata and Coal Seam Characteristicsmentioning
confidence: 92%
“…Previous studies have shown that the gas content increases with the coal rank, 45 , 46 which can be attributed to the increase of micropore and pore specific surface area. 47 The No. 16 coal seam may have higher gas contents than the No.…”
Section: Coal-bearing Strata and Coal Seam Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation